The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1093/nar/gkf627
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of HIV-1 infection in human peripheral blood mononuclear cells by specific RNA interference

Abstract: The RNA interference (RNAi) phenomenon is a recently observed process in which the introduction of a double-stranded RNA (dsRNA) into a cell causes the specific degradation of a mRNA containing the same sequence. The 21-23 nt guide RNAs, generated by RNase III cleavage from longer dsRNAs, are associated with sequence-specific mRNA degradation. Here, we show that dsRNA specifically suppresses the expression of HIV-1 genes. To study dsRNA-mediated gene interference in HIV-1-infected cells, we have designed six l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 36 publications
(11 reference statements)
1
61
0
Order By: Relevance
“…Therefore, the use of synthetic siRNAs provides a rapid and cost-effective tool for new anti-HIV-1 gene therapeutics. 19 The ability of siRNA to control ischemia reperfusion injury related transcription factors, apoptosis, oxidative stress molecules, and complement factors supports the observation that RNAi-based therapeutics epitomize a novel and promising strategy for the control of IRI. 20 …”
Section: Resultsmentioning
confidence: 82%
“…Therefore, the use of synthetic siRNAs provides a rapid and cost-effective tool for new anti-HIV-1 gene therapeutics. 19 The ability of siRNA to control ischemia reperfusion injury related transcription factors, apoptosis, oxidative stress molecules, and complement factors supports the observation that RNAi-based therapeutics epitomize a novel and promising strategy for the control of IRI. 20 …”
Section: Resultsmentioning
confidence: 82%
“…70,71 Additionally, RNAi-based therapies have been investigated for the treatment of human immunodeficiency virus (HIV) infection. Several early and late HIV-encoded RNAs including the TAR element, 84 tat, 50,85,86 rev, 50,85 gag, 87,88 env, 88 vif, 84 nef 84 and reverse transcriptase, 86 have been targeted by short RNAs in various cell lines and primary hematopoietic cells. A recent study has demonstrated sustained siRNA-mediated inhibition of HIV type 1 in terminally differentiated macrophages, which constitute an important reservoir of HIV in vivo.…”
Section: Potential Clinical Applications Of Short Rnasmentioning
confidence: 99%
“…HIV-1-specific siRNAs can inhibit infection in permanent cell lines, primary CD4 + T-cells and macrophages (Song et al, 2003). An event in the viral life cycle is inhibited after fusion and before reverse transcription (RT) (Brummelkamp et al, 2002), which has a crucial role in the processing of premature RNA and H1 (Myslinski et al, 2001) (Paddison et al, 2002;Paul et al, 2002;Sui et al, 2002), or the sense and antisense (tandem type) strands can be transcribed from two different pol III promoters in the same vector (Park et al, 2002). Furthermore, the siRNA duplexes are more potent inhibitors than the antisense RNAs.…”
Section: Hiv-1 Infection Is a Worldwide Disease That Requires Alternamentioning
confidence: 99%